The experiences of Aboriginal and Torres Strait Islander Bachelor of Midwifery students: An integrative literature review. Issue 1 (February 2021) - Coleman, Renae; Hartz, Donna; Dahlen, Hannah
Abstract: Issue: There is an underrepresentation of Aboriginal and Torres Strait Islander midwives across Australia and an inadequate number of graduating midwives to redress this. A major pillar for the Birthing on Country Model is maternity care workforce development. Aim: The purpose of this review is to examine the enablers and barriers that Aboriginal students experience while undertaking the Bachelor of Midwifery degree in Australia. Methods: A search of the literature was undertaken through electronic databases. When only three papers were found looking at the experiences of Aboriginal midwifery students the search was broadened to include Aboriginal undergraduate health students. Findings: The literature review reported a strong need for cultural safety in both the clinical and education systems. Students with access to cultural supports, relationships with Aboriginal mentors and academics and Aboriginal clinical placements felt empowered and were able to navigate the 'two worlds' in a meaningful way. Discussion: This review highlights a significant gap in the literature. Despite the expanded search terms to include Aboriginal health students, a relatively narrow range of papers were found. Interestingly, the combined search revealed similar themes: kinship, personal factors, and cultural issues. Conclusion: Empowering and supporting Aboriginal Peoples to become midwives is essential. While systems and societies aim for cultural safety, this review shows there is still a way to go. Further research is essential to decolonise higher education and health care systems, and provide strong, well supported pathways for Aboriginal midwifery students.